Undoing multiculturalism : resource extraction and Indigenous rights in Ecuador - Martínez Novo, Carmen, 1966- (Pitt Latin American series., 2021)
"President Rafael Correa (2007-2017) led the Ecuadoran Citizens' Revolution that claimed to challenge the tenets of neoliberalism and the legacies of colonialism. The Correa administration promised to advance Indigenous and Afro-descendant rights and redistribute resources to the most vulnerable. In many cases, these promises proved to be hollow. Using two decades of ethnographic research, Undoing Multiculturalism examines why these intentions did not become a reality, and how the Correa administration undermined the progress of Indigenous people. A main complication was pursuing independence from multilateral organizations in the context of skyrocketing commodity prices, which caused a new reliance on natural resource extraction. Indigenous, Afro-descendant, and other organized groups resisted the expansion of extractive industries into their territories because they threatened their livelihoods and safety. As the Citizens' Revolution and other "Pink Tide" governments struggled to finance budgets and maintain power, they watered down subnational forms of self-government, slowed down land redistribution, weakened the politicized cultural identities that gave strength to social movements, and reversed other fundamental gains of the multicultural era."--Publisher description.